Designing a Web-Based Psychological Intervention for Patients With Myocardial Infarction With Nonobstructive Coronary Arteries: User-Centered Design Approach - Humphries, Sophia Monica; Rondung, Elisabet; Norlund, Fredrika; Sundin, Örjan; Tornvall, Per; Held, Claes; Spaak, Jonas; Lyngå, Patrik; Olsson, Erik M G (JMIR Publications, 2020)
BackgroundThe involvement of patient research partners (PRPs) in research aims to safeguard the needs of patient groups and produce new interventions that are developed based on patient input. Myocardial infarction with nonobstructive coronary arteries (MINOCA), unlike acute myocardial infarction (MI) with obstructive coronary arteries, is presented with no significant obstructive coronary artery disease. Patients with this diagnosis are a subset of those diagnosed with traditional MI and often need more psychological support, something that is presently not established in the current treatment scheme in Swedish health care or elsewhere, to our knowledge. An internet-delivered intervention might offer patients with MINOCA the opportunity to access a psychological treatment that is tailored to their specific needs after MINOCA and could therefore supplement the existing medical care in an easily accessible format. ObjectiveThis paper aims to describe the development of a therapist-guided, internet-delivered psychological intervention designed specifically for patients with MINOCA. MethodsThe study used a participatory design that involved 7 PRPs diagnosed with MINOCA who collaborated with a team consisting of researchers, cardiologists, and psychologists. Intervention content was developed iteratively and presented to the PRPs across several prototypes, each continually adjusted and redesigned according to the feedback received. The intervention and experience of it were discussed by PRPs in a final meeting and then presented to a panel of 2 clinical psychologists and a cardiologist for further input. ResultsThe outcome of the collaboration between PRPs and the research group produced a web-based psychological 9-step program focusing on stress, worry, and valued action. The input from PRPs contributed substantially to the therapy content, homework tasks, interactive activities, multimedia, and design presentation. ConclusionsWorking with PRPs to develop an intervention for people with MINOCA produced a web-based intervention that can be further evaluated with the goal of offering a new psychological treatment option to a patient group currently without one. Direct contribution from PRPs enabled us to obtain relevant, insightful, and valuable feedback that was put towards the overall design and content of the intervention.